2021
DOI: 10.3389/fpsyt.2021.677975
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Empathy in Subtypes of Antisocial Individuals

Abstract: Cognitive empathy allows individuals to recognize and infer how others think and feel in social situations and provides a foundation for the formation and maintenance of mutually constructive relationships. It may seem intuitive to assume that individuals who engage in antisocial behavior, who disregard the rights of others, might have problems with cognitive empathy. However, careful examination of the literature suggests that any dysfunction in cognitive empathy associated with antisociality varies by subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…Regarding types of antisociality, individuals in the psychopathic type fail to implicitly engage in cognitive empathy when explicitly required. Individuals in the antisocial-only subtype appear able to engage in cognitive empathy, showing no differences on questionnaire or behavioral tasks that tap explicit cognitive empathy, but may display subtle difficulties accurately inferring the emotions of others [ 45 ]. It has been suggested that while psychopathy may generally interfere with metacognitive abilities (including attributing a mental state to others), individuals with high levels of psychopathy do not exhibit this deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding types of antisociality, individuals in the psychopathic type fail to implicitly engage in cognitive empathy when explicitly required. Individuals in the antisocial-only subtype appear able to engage in cognitive empathy, showing no differences on questionnaire or behavioral tasks that tap explicit cognitive empathy, but may display subtle difficulties accurately inferring the emotions of others [ 45 ]. It has been suggested that while psychopathy may generally interfere with metacognitive abilities (including attributing a mental state to others), individuals with high levels of psychopathy do not exhibit this deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Prior researches on schizophrenia patients have demonstrated impaired emotional empathy ( 40 , 77 ). Moreover, literatures have shown a relationship between premeditated aggression and psychopathic personality traits, with premeditated aggression being more associated with the latter than impulsive aggression ( 78 , 79 ). Individuals demonstrating lack of empathy, remorse, and guilt, alongside manipulative, callous, and grandiose behaviors ( 80 , 81 ) may exhibit premeditative aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This subpopulation commit more ASB than non-psychopathic individuals (Chang et al, 2021) and ASB is more proactive, which can be seen as purposeful and motivated by a specific goal (Cima and Raine, 2009;Gillespie et al, 2018). This purposeful use of violence can possibly be ascribed to specific impairments in mentalizing, which may primarily find its roots in decreased empathy and impairments in attention (i.e., attention bottleneck).…”
Section: Pathway 3: Reciprocity (Skill and Will) In Relation To Antis...mentioning
confidence: 98%
“…Returning to the reciprocal altruism theory, people need the skill to act reciprocal but also the will to do so. Research indicates that people with high CU traits do not show overall mentalizing impairments ( Wilson et al, 2011 ; Chang et al, 2021 ). There is some evidence that genetic etiologies underlie these high CU traits ( Moore et al, 2019 ).…”
Section: Pathway 3: Reciprocity (Skill and Will) In Relation To Antis...mentioning
confidence: 99%